Temperature effects on seed germination in races of common beans (Phaseolus vulgaris L.) = Efeitos da temperatura na germinação de sementes em culturas de feijões comuns (Phaseolus vulgaris L.) - Nelson Barbosa Machado Neto; Maria Regina Prioli; Ana Beatriz Gatti; Victor José Mendes Cardoso (Acta Scientiarum: Animal Sciences, 2010)
Temperature is one of the most important environmental factors, affecting establishment and crop development. Seed germination is particularly affected by temperature. The aim of this work was to evaluate the tolerance temperatures during germination in several bean cultivars. The seeds were submitted to temperatures rangingfrom 8 to 45°C in thermal block apparatus and primary root protrusion time. The number of germinated seedlings was scored for each cultivar and temperature. High temperatures (@40°C and upper) strongly inhibit cultivar germination, but 'IAPAR-57', ‘Guarumbé’ and ‘Iratim’ appear to be more sensitive to high temperature stress than others. ‘IAC Carioca 80SH’ PP and 'IAPAR-57' were less tolerant to low temperatures. The thermal time model could describe, relatively well, the time-course of the cultivars isothermal germination, which differed in the thermal time amount required to germinate. 'IAC Carioca-Akytã' needs fewer degrees per day to achieve germination than others, whereas the cultivar 'Campeão-1' requires more thermal time. A temperatura é um fator ambiental importante, afetando a germinação de sementes, o estabelecimento e o desenvolvimento de culturas. Oobjetivo deste trabalho foi avaliar as temperaturas de tolerância durante germinação em vários cultivares de feijão e determinar o valor de parâmetros térmicos para a germinação de cultivares. Sementes foram submetidas a temperaturas variando de 8°C a 45°C, em bloco termo-gradiente até a protrusão da raiz primária. Temperaturas altas (40°C ou mais) inibem fortemente a germinação dos cultivares. 'IAPAR-57, 'Guarumbé' e 'Iratim' parecem ser mais sensíveis à temperatura alta que outros. 'IAC Carioca 80SH ' PP e 'IAPAR-57' foram menos tolerantes a baixas temperaturas. O modelo termal de tempo poderia descrever relativamente bem o curso da germinação em isotermas dos cultivares que diferiram na quantia de graus-dia para germinar. 'IAC Carioca-Akytã' precisa de menos graus-dia-1 paraalcançar a germinação que outros, O cultivar' Campeão-1 requer mais graus-dia-1.